Permanent accompaniment in the sociocultural and emotional aspect in indigenous students of the Peruvian University Cayetano Heredia - Ampinti Shiñungari, Abelina (2025)
This research on the study of higher education of indigenous peoples provides strategies for permanent accompaniment to indigenous students with scholarships and educational credits (PRONABEC) of the Universidad Peruana Cayetano Heredia. The objective is to provide culturally relevant assistance and emotional support during the training process of students. The methodology is qualitative which analyzes concepts and elements of strategies used, allowing to describe behaviors of socio-environmental-cultural adaptation and experiences through the ethnographic technique that characterizes the study of 14 students of Bilingual Intercultural Education and 02 students ofthe professional career of Nursing. The results indicate that the continuous accompaniment of 18 students who began their studies, 16 continue studying the eighth cycle of the career. It is concluded that the tutoring developed with descriptive techniques and support excites.